Deskripsi Kecanduan Game Online Pada Remaja Di Kebun Cengkeh Rt.01/Rw.09 Desa Batu Merah Kecamatan Sirimau Kota Ambon - Ira Sandi Tunny (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Gamesis an activity done for fun or enjoyment that has rules so that someone wins and someone loses. Addiction to playing games excessively is known as Games Addiction. The aim of this research is to find out the description of online game addiction among teenagers in Kebun Cengkeh Rt.01/Rw.09, Batu Merah Village, Sirimau District, Ambon City in 2020. This research method is descriptive research. The sample in this study consisted of 51 teenagers located in Kebun Cengkeh Rt.01/Rw.09 Batu Merah Village, Sirimau District.This research has one variable, namely online game addiction. From the results of data analysis withFrequency distribution results showed that the level of online game addiction was mostly mild, as many as 24 respondents (47.1%) among teenagers in Kebun Cengkeh Rt.01/ Rw 09 Batu Merah Village. The conclusion is that it can be described that there is a medium level of online game addiction, severe online game addiction among teenagers in Kebung Cengkeh Rt.01/ Rw 09 Batu Merah Village.